Problemy percepcji idei zrównoważonego rozwoju w naukach przyrodniczych - Mizgajski, Andrzej (Problems of perceiving the sustainable development idea in natural sciences, 2007)
The background for analysis was the discussion of generał problems pertaining to the use of the sustainable development concept in scientific research. The concept is being incorporated into the notional structures of various disciplines of study in an incoherent manner, while no foundations for a new discipline that would combine ecological, economic and, socio-political aspects have yet been formed. Considering the relation between the naturę protection and the sustainable development idea, the former was divided into two complementary trends: conservative and utilitarian. The conservative approach is especially important whenever the level of knowledge is insufficient to ascertain benefits for humans or when rational arguments in favour of protecting natural values are ignored. The utilitarian trend - emphasizing the significance of different natural values to humans - permits to graduate and relate them to other ąualities, including social and economic ones. Developing the concept of ecosystems services is going to be particularly important as its aim is to show natural values in economic categories.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 171-179